PEMENUHAN HAK BURUH DALAM PEMBERIAN PESANGON MENURUT PASAL 43 PERATURAN PEMERINTAH 35 TAHUN 2021 - Turnip, Clarisa Fitri Milenia; Mardijono, H.R. Adianto (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The purpose of this research is to determine whether the rights of workers in providing severance pay according to article 43 of government regulation 35 of 2021. Fulfillment of rights is the obligation of every person to have rights which are everything that must be obtained by individuals because these rights are inherent in each of them. Same thing with work. It is known that government laws and regulations also limit workers and severance pay. Basically, a worker/labourer is a person who works in a company who has the right to receive an imbalance or wage from a company where he works, the company also has regulations and the government also provides regulations to employees. The company is known that the rules that have been set by the government are the ones that must be obeyed by every company. The existence of a working relationship with this company creates a working relationship between the worker and the entrepreneur that not only builds a relationship but also the company and the worker/laborer may experience termination of employment in that the worker/labourer is entitled to receive an imbalance or severance pay at the time the worker/laborer is working or at the end of the job. the relationship between the ape and the company is obliged to provide the workers' rights. In presenting these rights the company must fulfill a decent life for workers, because of the existence of laws and government regulations in order to create proper fulfillment of rights for workers/workers. The method used in this research is to use the legal and conceptual approach. In this study, it will be known whether the labor severance pay in Article 43 of Government Regulation 35 of 2021 is in accordance with the right to a decent life according to the 1945 Constitution of the Republic of Indonesia